KAJIAN PENGUATAN KOMUNITAS INTELIJEN DAERAH - Armaidy Armawi (Fakultas Hukum Universitas Gadjah Mada, 2013)
This study aims to disect Presidential Instruction No. 2 of 2002 and the Minister of Home Affairs Regulation No. 11 of 2006 by employing hermeneutic-juridical approach where we performed textual analysis of ‘legal aspirations’ and put it in the context of contemporary condition. We think fortification of the Local Intelligence Community must be attempted. Optimal coordination among Kominda members and coordination between security personnel and common society in responding to threats might affect the stability of local security. Synergic steps among several Kominda members are needed to improve their performance and strengthen the institution. Improvement of performance as well as reinforcement of Kominda members is needed to instill the sense of intelligence. Kajian ini bertujuan menelaah Instruksi Presiden Nomor 5 Tahun 2002 dan Peraturan Menteri Dalam Negeri No. 11 Tahun 2006 dalam rangka penguatan Komunitas Intelijen Daerah. Dalam kajian ini digunakan metode hermeneutik yuridis. Menafsirkan ”kehendak hukum” terhadap makna teks dalam konteks suasana kekinian. Optimalisasi koordinasi di antara anggota Kominda dan adanya kerjasama yang baik antara masyarakat dan aparat keamanan dalam mengantisipasi ancaman, akan membawa dampak pada stabilitas keamanan daerah. Diperlukan langkah yang sinergis dari beberapa anggota Kominda untuk dapat memperbaiki kinerja dan penguatan institusi. Perbaikan kinerja dan penguatan anggota Kominda perlu dilakukan agar memiliki sense of intelligence.